Torture Journal Annual Report 2017 - excerpts - Pérez-Sales, Pau; Witcombe, Nicola (Torture Journal, 2018)
Academia and funding bodies often require publication in journals with the highest Impact Factor and field workers and clinicians often seek practical dissemination methods. We continue to strive to fulfil these two parallel and we think not mutually exclusive aims. Torture Journal is a medical and psychological publication that aims to serve all professionals working with the rehabilitation of victims and prevention oftorture. Its objectives are to: • be a reference source for practitioners; • promote and lead research in the field; • foster debate on key topics within the scope of the journal; and, • be a collective expression of the whole sector and to facilitate networking. Additionally, the Torture Journal has always played and continues to play a crucial part of fulfilling the strategy of its publisher, the International Council for Rehabilitation for Torture Victims. This is most recently set out in one of the key outputs agreed by the IRCT Council in December 2017, the Global Knowledge Platform.